ANALISIS FAKTOR PENTING YANG MEMPENGARUHI KNOWLEGDE SHARING DI FAKULTAS ILMU KOMPUTER UNIVERSITAS MUHAMMADIYAH METRO - Wulandari, Ika Arthalia; Sukamasetya, Pristi; Siregar Pahu, Gunayanti Kemalasari (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2020)
Knowledge has become an asset in an organization, none other than knowledge in a group. The concept of knowledge sharing is an activity of exchanging knowledge between two or more parties such as individuals, groups, organizations or parts of an organization. In the world of education, the involvement of knowledge sharing among academicians can improve learning outcomes at a tertiary institution. The purpose of this study is to propose a model of knowledge sharing among academics at the University, especially academics at the Faculty of Computer Science, University of Muhammadiyah Metro, Lampung. Factors that influence knowledge sharing among academics consist of individual factors and technological factors. Both of these factors can improve the performance of learning outcomes in higher education